Cross-talk between cultural and genetic evolution in humans - Heyer, Evelyne (Henry Stewart Talks, 2015)
Impact of women migration on the population genetics, Different social organizations in Central Asia, Common ancestors study in Pastoralists from Central Asia, Impact of social organization on genetic diversity, Cultural transmission of reproductive success, Genetic adaptations to diet